Konseling Pencegahan Depresi Pada Ibu Rumah Tangga Dengan HIV/AIDS Di Kabupaten Cirebon - Titi Sri Suyanti; Sumarmi Sumarmi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
The problems that usually arise in people with HIV/AIDS (PLWHA) are that apart from physical problems, there is also stigma, namely the bad social reaction towards people with HIV/AIDS. Such complex problems in PLWHA are accompanied by loss of social support such as lack of attention from family and community. This reaction is a bad experience for PLWHA where when they need support there is no one to help them, so depression often occurs in PLWHA. Depression in HIV AIDS sufferers can increase the risk of non-adherence behavior towards treatment resulting in a high risk of shorter survival. Failure to recognize and treat depression in HIV/AIDS sufferers not only endangers the patient but also endangers society. Research related to depression in PLWHA at Cipto Mangunkusumo Hospital, Jakarta, found that more than half of the patients experienced depression, namely 51.1%. The general aim of providing this counseling is so that PLWHA are able to overcome the depression they are experiencing. The design used in this community service is counseling with communication, information and education methods. The targets of this community service activity are housewives with HIV/AIDS in Cirebon district. From the preliminary study carried out, it was found that data on the problems that arise among PLWHA in Cirebon district cannot be separated from the emergence of psychological problems, this occurs because of feelings of sadness, disappointment, shame, fear of being ostracized by friends and family and fear of being abandoned by their husbands.